Gendered processes of agricultural innovation in the Northern uplands of Vietnam - Kawarazuka, Nozomi; Prain, Gordon (Emerald Publishing Limited, 2019)
This paper aims to explore ethnic minority women’s gendered perceptions and processes of agricultural innovation in the Northern uplands of Vietnam. The key research question asks how women develop innovations and learn new agricultural practices within patriarchal family structures.